Differentially Expressed MicroRNAs in the Development of Early Diabetic Retinopathy. (15th June 2017) - Gong, Qiaoyun; Xie, Jia'nan; Liu, Yang; Li, Ying; Su, Guanfang
Abstract : The pathological mechanisms of diabetic retinopathy (DR), a leading cause of blindness in adults with diabetes mellitus, remain incompletely understood. Because microRNAs (miRNAs) represent effective DR therapeutic targets, we identified aberrantly expressed miRNAs associated with cellular dysfunction in early DR and detected their potential targets. We exposed human retinal endothelial cells (HRECs) and a cell line of retinal pigment epithelial (RPE) cells to high glucose (25 mmol/L, 1–7 days) to mimic DR progression and used streptozotocin-injected rats (4–8 weeks) for an in vivo diabetes model. HREC/RPE viability decreased after 24 h incubation and diminished further over 6 days, and Hoechst staining revealed hyperglycemia-induced HREC/RPE apoptosis. Although miR-124/-125b expression decreased with DR progression in vitro and in vivo, miR-135b/-199a levels decreased in retinal cells under hyperglycemia exposure, but increased in diabetic retinas. Moreover, miR-145/-146a expression decreased gradually in high-glucose-treated HRECs, but increased in hyperglycemia-exposed RPE cells and in diabetic rats. Our findings suggested that aberrant miRNA expression could be involved in hyperglycemia-induced retinal-cell dysfunction, and the identified miRNAs might vary in different retinal layers, with expression changes associated with DR development. Therefore, miRNA modulation and the targeting of miRNA effects on transcription factors could represent novel and effective DR-treatment strategies.